Public health communication: Attitudes, experiences, and lessons learned from users of a COVID-19 digital triage tool for children - Michel, Janet; Rehsmann, Julia; Mettler, Annette; Starvaggi, Carl; Travaglini, Nicola; Aebi, Christoph; Keitel, Kristina; Sauter, Thomas C. (Frontiers in Public Health, 2022)
Background The pandemic has made public health communication even more daunting because acceptance and implementation of official guidelines and recommendations hinge on this. The situation becomes even more precarious when children are involved. Our child-specific COVID-19 online forward triage tool (OFTT) revealed some of the public health communication challenges. We aimed to explore attitudes, experiences, and challenges faced by OFTT users and their families, in regard to public health recommendations. Methods We selected key informants (n = 20) from a population of parents, teachers, guardians, as well as doctors who had used the child-specific COVID-19 OFTT and had consented to a further study. Videos rather than face-face interviews were held. Convenience and quota sampling were performed to include a variety of key informants. Interviews were recorded, transcribed verbatim, and analyzed for themes. Results Several themes emerged, namely; (1) definition and expectations of high-risk persons, (2) quarantine instructions and challenges, (3) blurred division of responsibility between authorities and parents, (4) a novel condition and the evolution of knowledge, (5) definition and implications of socioeconomic status, (6) new normal and societal divisions, and (7) the interconnectedness of these factors-systems thinking. Conclusion As the virus is evolving and circumstances are changing rapidly, the communication of public health to the different interest groups becomes, both an art and science, even more so when using a new technological communication channel: an OFTT. A myriad of interconnected factors seems to influence attitudes toward public health recommendations, which calls for systems thinking in public health communication.